Resurrection and Death From Rabbinic Understandings to the Theology of Edward Schillebeeckx - Zhai, Yujia (Lumen et Vita, 2017)
My paper will explore the understanding of death and resurrection in Judaism through the selections from biblical and rabbinic corpus and reflect on its relevance to Catholic theology on the same subject matter. The diverse, unsystematic, and contextual characters of Jewish remarks on death and resurrection suggest that these remarks are rooted in the more fundamental concern regarding covenantal relationship and ethical living. Resurrection is mostly presented as an extended reflection of Jewish concern for the justice and righteousness in this world, following the traditional Jewish hermeneutical principle “kal vahomer.” Death, likewise, is understood as indicative of the condition of the living world as well as contributive to the development of Jewish religious traditions and identities. Thus, in Judaism, death is neither completely negative nor utterly overshadowed by the sure hope of resurrection. In some significant ways, the Jewish understanding of death and resurrection correspond to 20th century catholic theological reflections. Edward Schillebeeckx, for example, suggests that belief in resurrection does not argue away the realty of death but rather let death be death. As a free gift of God to those who trust, resurrection makes sense of human death, rather than simply declaring it powerless or inconsequential. Thus, Schillebeeckx asserts that it is important to focus not just on Jesus's final resurrection but also on Jesus’ entire life which led up to his death. Jesus’ death itself is an invitation to the participation of Jesus’ entire life, and is therefore also a hermeneutical opening for the development of Christian religious traditions and identities. In conclusion, though Jesus’ death and resurrection are unprecedented and unparalleled revelations, they should not supersede a Jewish understanding of death and resurrection or render them primitive. Rather, death and resurrection are a signature component of the common root of Christianity and Judaism.